Pengaruh Penambahan Titanium Terhadap Kekuatan Material Baja Sebagai Bahan Shielding Alutsista Pertahanan - Ahmada, Mufti Labib; Aritonang, Sovian; Murniati, Riri (Rekayasa Material, Manufaktur dan Energi, 2024)
The addition of titanium to steel materials has been a significant research focus in the metallurgical industry. This research aims to investigate the effect of titanium addition on the mechanical and structural properties of steel. Titanium is an interesting element in this context because it has properties that can improve the performance of steel, such as strength, corrosion resistance, and resistance to high temperatures. The addition of titanium to various types of steel has been shown to increase their strength and mechanical properties, primarily by forming titanium carbide or sulfide deposits that reduce grain growth and increase toughness and high temperature resistance. This could open up opportunities to develop high-strength steel with the addition of titanium for applications that require superior mechanical properties, such as for shielding defense equipment.